Simplified flow cytometry-based assay for rapid multi-cytokine profiling and machine-learning-assisted diagnosis of inflammatory diseases - Quan, Qiang; Ju, Xuegui; Li, Guangmei; Ye, Lu; Ren, Sichong; Yang, Shuxin; Zhang, Rui; Wang, Hui; Lin, Ruyue; Yu, Luoting (Frontiers in Pharmacology, 2025)
IntroductionMultiple cytokines detection represents a more robust way to predict the disease progression than a single cytokine, and flow cytometry (FCM)-based assays are increasingly used worldwide for multiple cytokines profile.MethodsInspired by One-step concept of ELISA technology, here we reported the development of one-step FCM-based 12-plex cytokine assay to reduce operation and reaction times, in which all the reagents (including capture-antibody-modified beads and phycoerythrin-labeled detection antibodies) had mixed in the same reaction system and achieved similar performance to the conventional approach. Moreover, we used the lyophilization technique to remove the need for cold storage of reagents to further simplify the assay procedure.ResultsWe leveraged our technology to test clinical serum samples from patients with COVID-19 or HBV infectious diseases, and established supervised or unsupervised machine learning models to predict the severity or viral load and get deeper insights into the diseases.DiscussionTogether, our results demonstrate a general and framework for convenient analysis of cytokine panel and have the potential to influence medical research and application in this field.